2021
DOI: 10.3390/jtaer16040049
|View full text |Cite
|
Sign up to set email alerts
|

Pricing and Profit Management Models for SaaS Providers and IaaS Providers

Abstract: Cloud computing has rapidly penetrated enterprise and user computing markets with three prominent service models: software as a service (SaaS), platform as a service (PaaS), and infrastructure as a service (IaaS). Cloud computing has also proven to be one of the most important environmentally sustainable technological innovations in the year of Industrial Revolution 4.0. While SaaS and IaaS are the two largest revenue generating services in the cloud service market, the pricing and profit generating mechanisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Several dynamic pricing models have been conducted based on game theory [20][21][22][23][24][25]. In [20], the authors suggested a framework for the cloud computing market to make the market uniform and competitive, whereby users can purchase resources from different companies and flexibly exchange their idle resources.…”
Section: Related Workmentioning
confidence: 99%
“…Several dynamic pricing models have been conducted based on game theory [20][21][22][23][24][25]. In [20], the authors suggested a framework for the cloud computing market to make the market uniform and competitive, whereby users can purchase resources from different companies and flexibly exchange their idle resources.…”
Section: Related Workmentioning
confidence: 99%
“…Hybrid Cloud: Capacity to adapt to existing technological systems hosted on company premises. This makes it possible for the most critical processes for the business to be carried out locally, while other processes are carried out through the platform [19,33,34].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Under this general trend, a new model-sharing economy has emerged. This way of trading on the Internet has become a trend and inevitable choice 1,2 . Virtual goods are one of the topics that have emerged and become popular in recent years.…”
Section: Introductionmentioning
confidence: 99%